A STUDY ON “THE EFFECTS PROJECT BASED LEARNING STRATEGY ON ACADEMIC ACHIEVEMENT AMONG HIGH SCHOOL STUDENT” - Elizabath, G. Sudha; Sangeetha, T. (International Journal of Research -GRANTHAALAYAH, 2018)
In India most of the classrooms are still teacher centered, where the students have to sit and listening to the teachers lecture. In emerging 21st century the student’s needs to develop skills like reasoning, problem-solving, creative, collaboration, critical thinking, communication etc., the study aimed to examine the Project Based Learning method in teaching high school students. The investigator adopted experimental method to study the PBL method in teaching high school students. For the study sample of 60 IX std students from schools situated in Coimbatore district in Tamil Nadu was selected. The finding reveals that is inferred that there is a difference between PBL method of teaching and conventional teaching among High school’s students.